The Effect Of Group Guidance With Symbolic Modelling Techniques On Raising Awareness Of The Importance Of Adhering To Health Protocols Covid-19 - Susanti, Rizki (Prosiding University Research Colloquium, 2021)
The purpose of this study is to see how group guidance combined with symbolic modelingtechniques affects the importance of adhering to health protocols covid-19. This study wascarried out on pt teenagers. Nusantara Plantation IV Plantation of Sosa II Emplasmen.This study is a Pseudo Experiment with a One Group Pretest and Posttest research design.Purposive sampling was used to select study participants. As many as six teenagers weresampled. The data collection method employs a scale of awareness of the importance ofadhering to health protocols covid-19. ANOVA (Analysis of Variance) data analysistechniques are used with the spss 24 for Windows program. Adolescents between the agesof 15 and 17 were studied. The findings of this study revealed that using symbolic modelingtechniques to guide groups influenced the increase in awareness of the importance ofadhering to health protocols. covid-19. When the statistical Parametric One Way Anovatest results show p=0.000<0,05 and the probability result is less than 0.05, Ho is rejected.This study's findings also revealed a difference in the percentage increase in posttestexperimental groups (15.62% ).